Conservatives without conscience - Dean, John Wesley 1938- (New York Penguin, 2007)
Charges the Bush administration with using religious morality and propaganda-like tactics to promote big business interests and silence alternate perspectives at the expense of the nation's constitutional foundations.
"First published in the United States of America by Viking Penguin, a member of Penguin Group (USA) Inc., 2006."--T.p. verso.
CSSP-6986 donated by Lewanda Lim, Gahanna, Ohio.
Keywords: Republican Party (U.S. : 1854- ); Conservatism -- United States; United States -- Politics and government -- 2001-.